LGBTQ Teacher’s Identities Within Heteronormative SchoolEnvironments - España Delgado, José Antonio (Universidad Pedagógica y Tecnológica de Colombia, 2022)
LGBTQ teachers face multiple challenges throughout their professional life as a result of pervasiveheteronormative school environments or heteronormativity in general. Nevertheless, LGBTQ teachers'realities remain somewhat undiscussed and underexplored, especially in Colombia. This articlereflects upon the way LGBTQ educators' identities are hindered by heteronormative workplaceclimates and addresses actions that might lead to the (re)construction of more supportive schoolenvironments in Colombia.